2021
DOI: 10.3390/cancers13194801
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Inhibition of Sphingosine-1-Phosphate Signaling in HIF-2α Inhibitor-Resistant Clear Cell Renal Cell Carcinoma

Abstract: Specific inhibitors of HIF-2α have recently been approved for the treatment of ccRCC in VHL disease patients and have shown encouraging results in clinical trials for metastatic sporadic ccRCC. However, not all patients respond to therapy and pre-clinical and clinical studies indicate that intrinsic as well as acquired resistance mechanisms to HIF-2α inhibitors are likely to represent upcoming clinical challenges. It would be desirable to have additional therapeutic options for the treatment of HIF-2α inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The development of belzutifan is a major advance in the treatment of RCC, but preclinical studies revealed that some RCC cell line–derived tumors and patient-derived xenografts showed resistance to HIF-2 inhibitors ( 162 , 164 ). One mouse model of RCC that was resistant to PT2385 responded to treatment with acriflavine ( 169 ), which binds to HIF-2α (and HIF-1α) at a site different from that of PT2385 ( 47 , 170 ). There are multiple registrations for clinical trials involving belzutifan at ClinicalTrials.gov ( Supplemental Table 4 ).…”
Section: Targeting Hifs For Cancer Therapymentioning
confidence: 99%
“…The development of belzutifan is a major advance in the treatment of RCC, but preclinical studies revealed that some RCC cell line–derived tumors and patient-derived xenografts showed resistance to HIF-2 inhibitors ( 162 , 164 ). One mouse model of RCC that was resistant to PT2385 responded to treatment with acriflavine ( 169 ), which binds to HIF-2α (and HIF-1α) at a site different from that of PT2385 ( 47 , 170 ). There are multiple registrations for clinical trials involving belzutifan at ClinicalTrials.gov ( Supplemental Table 4 ).…”
Section: Targeting Hifs For Cancer Therapymentioning
confidence: 99%
“…Due to the anti-apoptotic and pro-angiogenic roles of S1P, the SphK/S1P/S1PR axis attracts special interest in cancer treatment [ 23 ]. More specifically, this axis seems to be a master regulator of hypoxia by regulating HIF-1α and HIF-2α protein levels in human cancer cell lines including VHL-deficient ccRCC [ 24 ].…”
Section: Sphingolipids In Renal Cancermentioning
confidence: 99%
“…Fingolimod (FTY720) which is an approved immunomodulator for the treatment of multiple sclerosis, acts as an unspecific agonist of all S1P receptors, except S1P 2 , and as a functional antagonist of S1P 1 [ 38 ]. In several HIF-2α-resistant ccRCC cell lines, as well as in HIF-2α-resistant mouse ccRCC models, FTY720 showed anti-proliferative and anti-tumor effects [ 24 ]. Whether the modulation of all S1PRs or only one of them is needed for these actions is not well understood.…”
Section: Sphingolipids In Renal Cancermentioning
confidence: 99%
See 2 more Smart Citations